MEMOTRET KERAWANAN PANGAN DENGAN METODE HFIAS (Studi Kasus Di Salah Satu Desa Hutan Di Desa Lembu Kecamatan Bancak, Kabupaten Semarang) - Daru Purnomo (Universitas Kristen Satya Wacana, 2015)
Food security is the nation's wealth and richness of farmers in the past, that now are decrease even disappear- replaced with production patterns and food-paced consumtive patterns, as a result of the introduction from the interests of neo-liberazation globalization farm that seems to be very